Just me - Ets, Marie Hall, 1895- (New York : Viking, 1965)
A little boy imagines he can match the antics of his animal friends as he spends an afternoon at solitary play.
Caldecott Honor
2.4
K-3
Keywords: Animals -- Fiction; Animals -- Fiction